What Is the Best Evidence to Guide Management of Acute Achilles Tendon Ruptures? A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials. Issue 10 (28th October 2021) - Meulenkamp, Brad; Woolnough, Taylor; Cheng, Wei; Shorr, Risa; Stacey, Dawn; Richards, Megan; Gupta, Arnav; Fergusson, Dean; Graham, Ian D.
Abstract: Background: Uncertainty exists regarding the best treatment for acute Achilles tendon ruptures. Simultaneous comparison of the multiple treatment options using traditional study designs is problematic; multiarm clinical trials often are logistically constrained to small sample sizes, and traditional meta-analyses are limited to comparisons of only two treatments that have been compared in head-to-head trials. Network meta-analyses allow for simultaneous comparison of all existing treatments utilizing both direct (head-to-head comparison) and indirect (not previously compared head-to-head) evidence. Questions/purposes: We performed a network meta-analysis of randomized controlled trials (RCTs) to answer the following questions: Considering open repair, minimally invasive surgery (MIS) repair, functional rehabilitation, or primary immobilization for acute Achilles tendon ruptures, (1) which intervention is associated with the lowest risk of rerupture? (2) Which intervention is associated with the lowest risk of complications resulting in surgery? Methods: This study was conducted with methods guided by the Cochrane Handbook for Systematic Reviews of Interventions and is reported in adherence with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension statement for incorporating network meta-analysis. Five databases and grey literature sources (such as major orthopaedic meeting presentation lists) were searched from inception to September 30, 2019. Included studies were RCTs comparing treatment of acute Achilles tendon ruptures using two or more of the following interventions: primary immobilization, functional rehabilitation, open surgical repair, or MIS repair. We excluded studies enrolling patients with chronic ruptures, reruptures, and preexisting Achilles tendinopathy as well as studies with more than 20% loss to follow-up or less than 6 months of follow-up. Nineteen RCTs (1316 patients) were included in the final analysis. The mean number of patients per study treatment arm was 35 ± 16, mean age was 41 ± 5 years, mean sex composition was 80% ± 10% males, and mean follow-up was 22 ± 12 months. The four treatment groups were compared for the main outcomes of rerupture and complications resulting in operation. The analysis was conducted using random-effects Bayesian network meta-analysis with vague priors. Evidence quality was evaluated using Grades of Recommendation, Assessment, Development, and Evaluation methodology. We found risk of selection, attrition, and reporting bias to be low across treatments, and we found the risk of performance and detection bias to be high. Overall risk of bias between treatments appeared similar. Results: We found that treatment with primary immobilization had a greater risk of rerupture than open surgery (odds ratio 4.06 [95% credible interval CrI 1.47 to 11.88]; p < 0.05). There were no other differences between treatments for risk of rerupture. Minimally invasive surgery was ranked first for fewest complications resulting in surgery and was associated with a lower risk of complications resulting in surgery than functional rehabilitation (OR 0.16 [95% CrI 0.02 to 0.90]; p < 0.05), open surgery (OR 0.22 [95% CrI 0.04 to 0.93]; p < 0.05), and primary immobilization (OR < 0.01 [95% CrI < 0.01 to 0.01]; p < 0.05). Risk of complications resulting in surgery was no different between primary immobilization and open surgery (OR 1.46 [95% CrI 0.35 to 5.36]). Data for patient-reported outcome scores and return to activity were inappropriate for pooling secondary to considerable clinical heterogeneity and imprecision associated with small sample sizes. Conclusion: Faced with acute Achilles tendon rupture, patients should be counseled that, based on the best-available evidence, the risk of rerupture likely is no different across contemporary treatments. Considering the possibly lower risk of complications resulting in surgery associated with MIS repair, patients and surgeons must balance any benefit with the potential risks of MIS techniques. As treatments continue to evolve, consistent reporting of validated patient-reported outcome measures is critically important to facilitate analysis with existing RCT evidence. Infrequent but serious complications such as rerupture and deep infection should be further explored to determine whether meaningful differences exist in specific patient populations. Level of Evidence: Level I, therapeutic study.